SPE Middle East Oil and Gas Show and Conference 2013
DOI: 10.2118/164241-ms
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming Design Challenges of Chemical EOR in High-Temperature, High Salinity Carbonates

Abstract: The optimization of chemical floods for a low-permeability, high-salinity, high-temperature carbonate formation presents several unique design challenges, which may be overlooked in short coreflood experiments. Low permeability formations require the optimization of polymer molecular weight distribution such that both mobility reduction and injectivity are maximized. The effects of high core-scale heterogeneity must be understood and mitigated, for example, by increasing core length. These subjects are explore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Moreover, when temperatures exceed 60 C, the acrylamide groups within the HPAM polymer hydrolyze to form acrylate clusters. Furthermore, when temperatures exceed 75 C and there is a proximity of divalent cations, the degree of hydrolysis rapidly increases, triggering precipitations [ 99 , 100 , 101 , 102 ]. Additionally, it was noticed that the polymers with a greater degree of hydrolysis at the start tend to precipitate much faster, and this precipitation is even more aggravated at higher temperature and salinity/hardness [ 66 , 68 , 72 ].…”
Section: Potential Polymer Types Suitable For Hths Carbonate Reservoirsmentioning
confidence: 99%
“…Moreover, when temperatures exceed 60 C, the acrylamide groups within the HPAM polymer hydrolyze to form acrylate clusters. Furthermore, when temperatures exceed 75 C and there is a proximity of divalent cations, the degree of hydrolysis rapidly increases, triggering precipitations [ 99 , 100 , 101 , 102 ]. Additionally, it was noticed that the polymers with a greater degree of hydrolysis at the start tend to precipitate much faster, and this precipitation is even more aggravated at higher temperature and salinity/hardness [ 66 , 68 , 72 ].…”
Section: Potential Polymer Types Suitable For Hths Carbonate Reservoirsmentioning
confidence: 99%
“…With this results, it can be discarded losses of surfactant as an issue on the performance of the technique inside of the reservoir, additionally, the area that covered went from the center to the producers indicating a good movement of the surfactant through the reservoir especially in the direction of producers 1 and 2. This movement indicated that in this wells, if a surface facility was built, they will be the first requiring microemulsion treatments because of the arrival of the emulsion front (LEVITT et al, 2013). Moreover, the incremental oil volumes given by the SP when compared to the PF were related to this IFT reduction.…”
Section: Polymer Flooding Parametersmentioning
confidence: 90%
“…Later Levitt et al (2013), evaluated on a laboratory scale the challenges of SP flooding in a low permeability carbonate with high temperature and salinity conditions. The methodology consisted of the selection of polymer and surfactants, to later evaluate their performance on different core plugs: limestones, sandstone, and original reservoir cores.…”
Section: Laboratory Tests Of Sp Flooding On High Salinity And/or Carbmentioning
confidence: 99%